Analisa Pengendalian Persediaan Barang Dengan Perbandingan Metode Economic Order Quantity (EOQ) dan Just In Time (JIT) di PT. Astra Otoparts Tbk (Studi Kasus: Shop & Drive Sunter 1) - Priambudi, Bowo; Kholil, Muhammad (Universitas Mercu Buana, 2021)
This study aims to find out how the tire inventory control system is regulated according to current company policies and to find out how much the cost of merchandise inventory is Bridgestone Ecopia EP150 185/70R14, Bridgestone Ecopia EP150 175/65R14, Bridgestone Ecopia EP150 185/65R15 and Bridgestone Ecopia EP150 205/65R16 at Shop & Drive Sunter 1 for a period of 1 year (August 2021 – July 2022) then compare them using the Economic Order Quantity (EOQ) method and the Just In Time (JIT) method. The results of calculations using the Economic Order Quantity (EOQ) method are more effective and efficient if the company can optimize every aspect of inventory procurement including economical purchases, purchase frequency, safety stock. So get a total cost of Rp. 98,183,928 with an efficiency of Rp. 10,265,407.